2016
DOI: 10.15632/jtam-pl.54.1.229
|View full text |Cite
|
Sign up to set email alerts
|

Delamination properties of the human thoracic arterial wall with early stage of atherosclerosis lesions

Abstract: The aim of this work is to determine mechanical properties of interfaces between layers of the human thoracic aortic wall with early stages of atherosclerosis lesions. Circumferential (n = 48) and axial (n = 15) specimens have been prepared and the mechanical properties of the interfaces between the layers have been determined on the basis of the peeling test. The results show that the mechanical and dissection properties of the interfaces between the layers depend on the direction of the tests. The results co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…The standard deviation of peel tension within the plateau region was evaluated to assess the degree of fluctuation during the peeling process. The average peel tension was significantly higher (p < 0.01) for samples aligned axially versus circumferentially (97.0 6 12.7 versus 68.8 6 14.2 mN/mm, respectively) with an anisotropy ratio of 1.4, similar to the results reported by others [29,30]. The standard deviation of peel tension showed similar anisotropy (p < 0.001) for samples aligned axially versus circumferentially (12.66 6 2.22 versus 5.78 6 1.04 mN/mm, respectively).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The standard deviation of peel tension within the plateau region was evaluated to assess the degree of fluctuation during the peeling process. The average peel tension was significantly higher (p < 0.01) for samples aligned axially versus circumferentially (97.0 6 12.7 versus 68.8 6 14.2 mN/mm, respectively) with an anisotropy ratio of 1.4, similar to the results reported by others [29,30]. The standard deviation of peel tension showed similar anisotropy (p < 0.001) for samples aligned axially versus circumferentially (12.66 6 2.22 versus 5.78 6 1.04 mN/mm, respectively).…”
Section: Resultssupporting
confidence: 89%
“…Stresses near an advancing dissection include a combination of radial tension ðr rr Þ and transmural shear ðr rh ; r rz Þ [25], which are more difficult to test experimentally. Peel tests on pieces of artery [26][27][28][29] or aneurysm [30] provide insight into the failure behavior of the tissue in radial tension (r rr ), loading perpendicular to the medial lamella, as does direct extension to failure in the radial direction [26]. To examine transmural shear stresses ðr rz ; r rh Þ, the shear lap test, well established in the field of adhesives [31] and used by Gregory et al [32] to study interlamellar mechanics of the annulus fibrosus of the intervertebral disk, is an attractive option.…”
Section: Introductionmentioning
confidence: 99%
“…Kozuń [66] showed that the dissection properties are direction dependent also for stage II atherosclerotic aortas (classification according to Stary [133]), in particular the force per width F/w and the dissection energy W diss were higher in the longitudinal direction. In addition, a significantly higher dissection energy W diss for the adventitia/media + intima (A-MI) interface compared to the adventitia + media/intima (AM-I) interface was reported.…”
Section: Tissue Strength Quantificationmentioning
confidence: 99%
“…In addition, a significantly higher dissection energy W diss for the adventitia/media + intima (A-MI) interface compared to the adventitia + media/intima (AM-I) interface was reported. Following Kozuń [66], Kozuń[67] found the dissection energy for A-MI and AM-I interfaces in both circumferential and longitudinal directions to decrease with later stages of atherosclerosis (classification according to Stary [133]) until stage IV, whereas stages V and VI were characterized by an increase in the energy. Tong et al [143] reported a decreased dissection energy for the media/intima (MI) composite as well as a decreased anisotropy with increasing ILT age.…”
Section: Tissue Strength Quantificationmentioning
confidence: 99%
“…Despite the relevant incidence and high mortality, the biomechanics of this pathology remains unclear. Some studies have performed dissection tests on the medial layer of different arteries [1,2], others have studied the dissection behaviour of different layers in a specific location [3,4]. So far, no study has reported a complete dissection study, including the behaviour through different locations of the vessel and dissection between all layers.…”
Section: Introductionmentioning
confidence: 99%